Application Of Intravenous Fluid Warming Element Therapy In Reducing Symptoms Of Hypothermia In Postoperative SC Patients Through The Roy Adaptation Model Theory Approach In The Recovery Room Of The Operating Room Rs Ummi Bengkulu Year 2024 - AZ, Kurnia Lesmana; Epriana, Meri (Utami Publisher, 2025)
Hypothermia is a condition where the internal body temperature is below 36 degrees Cena the body's own temperature regulation mechanism experiences cold temperature pressure. Providing warm infusion fluids can be given to pre to post-operative patients in a way that is easy, practical and inexpensive as well as safe and effective to reduce the incidence of hypothermia in post-operative patients. This study aims to determine how the response and changes in temperature of patients using warm infusion to prevent hypothermia in patients post sectiocaesarea surgery with spinal anaesthesia based on Roy Adaptation theory in the kamae surgery room Ummi Hospital Bengkulu in 2024. Researchers chose the object of research is a maternal patient who is undergoing treatment in the hospital, by observing and interviewing directly the incidence of hyperthermia in patients with post SC surgery. Through qualitative research researchers can recognise the subject, feel what they experience in their daily lives. This research expected to describe various things related to the problem to be discussed about the application of warming element therapy. problems that will be discussed about the application of intravenous warming element therapy in reducing hypothermia symptoms in postoperative patients. intravenous fluid in reducing the symptoms of hypothermia in postoperative patients. SC through the Roy Adaptation model theory approach in the operating room of RSU Ummi Bengkulu. To determine the validation of the research results and so that they can be tested the authenticity and correctness of the data by various related parties, it is necessary to have an effort to validate the research results. form of effort to validate the research results. In testing the validity of data research results can be done by applying a standard of trust or trust test of the research data. Giving the element intravenous fluid warming element has a significant effect on reducing symptoms of hypothermia in postoperative SC patients. Patients who experience postoperative SC hypothermia are recommended to be given therapy by giving an intravenous intravenous fluid warming element.